The timing of 52-week high price and momentum - Bhootra, Ajay; Hur, Jungshik (Journal of Banking & Finance, 2013)
We propose a new momentum strategy based on the timing of a stock’s 52-week high price. We find that the stocks that attained the 52-week high price in the recent past significantly outperform the stocks that attained the 52-week high price in the distant past. In particular, the top 10% of the stocks with the most recent 52-week high price outperform the bottom 10% of the stocks with most distant 52-week high price by 0.70% per month. Further, conditioning on the recency of 52-week high price significantly increases the profitability of momentum strategy based on the nearness of current price to the 52-week high price. Specifically, the average monthly return of this strategy is about twice as large for stocks with recent 52-week high price as compared with stocks with distant 52-week high price.